ANALISIS KUALITAS PELAYANAN PUBLIK DALAM PENERIMAAN PAJAK KENDARAAN BERMOTOR PADA SISTEM ADMINISTRASI MANUNGGAL SATU ATAP (SAMSAT) MAL BUMI KEDATON KOTA BANDAR LAMPUNG - Agustuti Handayani; Hepiana Patmarina; Ria Rizka (e-JKPP, 2022)
The problems in this study are: (1) How is public service in motor vehicle tax receipts at the Office of the One-Stop Administration (Samsat) Ladies Mal Bumi Kedaton Bandar Lampung City. (2) What aspects hinder the implementation of public services in motor vehicle tax receipts at the Office of the One-Stop Administration (Samsat) Ladies Mal Bumi Kedaton Bandar Lampung City.The research method used is qualitative research with descriptive analysis method. The use of this method is to examine and describe qualitatively, how the quality of public services in motor vehicle tax receipts in the One Roof Manunggal Administration System (Samsat) of the Bumi Kedaton Mall Ladies. All data were obtained directly from informants in the field using interview and observation techniques, according to the research objectives to be achieved.The results showed that the service in paying motorized vehicle taxes in the One Roof Manunggal Administration (Samsat) Ladies Mal Bumi Kedaton Bandar Lampung City, namely, (1) Reliability, namely the apparatus has carried out their duties professionally, by providing services according to the main tasks and functions, although still there are people who want better service. (2) Responsiveness, always providing services to the community according to their duties, (3) Certainty, that the apparatus has implemented existing regulations by giving sanctions to people who are late in paying taxes, (4) Empathy, Providing socialization assistance and making it easier to pay motor vehicle taxes , without reducing the specified conditions, the community has also felt helped by what the apparatus has done. (5) In the form of, the apparatus in carrying out their duties always shows their identity as officers who provide services to the community, and carry out according to their main duties and responsibilities.